Murine hippocampal neuronal culture characterization as a model for the study of NRGs/ErbB4 signaling - Monge-Mora, Luis Felipe (2021)
Neuregulins (NRGs) comprise a family of EGF-like growth factors that modulate diverse cellular responses by interacting with their receptors ErbBs. In the Central Nervous System (CNS) the principal members include NRG1 and NRG2, and their principal receptor is ErbB4. The NRG1/ErbB4 signaling has been involved in relevant processes for the development and maintenance of the CNS such as interneuron migration, myelinization, neurotransmission, and synapse modulation. NRG2 can also bind to ErbB4 and activate it. However, the NRG2/ErbB4 signaling remains less studied. There is evidence that functional disturbances in these signaling modules could lead to neuronal networks dysfunction. Therefore, a characterized in vitro model in terms of the neuronal population in which these proteins are expressed, and their gene expression is greatly important for the study of NRG/ErBb4 signaling. Here we determined an approximate proportion of 85% glutamatergic neurons and 15% GABAergic interneurons in hippocampal cultures, prepared from C57BL/6 mice in embryonic (E) day 18, similar to the proportion reported in the hippocampus in vivo. We also determined the expression of Nrg1 type III, Nrg2 and ErbB4 genes by the 7th day in vitro (DIV).  Nrg1 type III had higher expression levels than Nrg2. Together, these results suggest that these cultures can be used as a valid model for the study of NRGs signaling in vitro.